Application of Sharia Principles in Religious Court Decisions in Divorce - Abdul Halim; Ajrina Tamimi; Andika Wahyu Yudhana; Alya Rahmah (Haqqiyyah: Journal of Islamic and Legal Studies, 2025)
The process of applying sharia principles to divorce decisions made by religious courts entails interpreting Islamic law and applying humanitarian and just considerations. This study finds that religious court judges apply the maqasid shariah principles particularly hifz nafs and hifz nasl in adjudicating divorce cases, especially those involving domestic violence or neglect. In addition, challenges and considerations in applying these sharia principles in handling divorce cases will also be discussed, as well as efforts to ensure that religious court decisions are in accordance with the values of applicable Islamic law and provide justice for all parties involved.